(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Cisplatin is a major antineoplastic drug for the treatment of solid tumors. Nephrotoxicity is dose- limiting side effect associated with clinical use of cisplatin. The present study was executed to determine whether bartogenic acid containing fraction of Barringtonia racemosa fruits (BREAF) possesses a nephroprotective effect against cisplatin-induced nephrotoxicity in rats. Furthermore, the study was also aimed to explore the mechanisms underlying this effect of BREAF. The BREAF was orally administered at the doses of (2, 5 and 10 mg/kg) for five consecutive days following single dose administration of cisplatin (5 mg/kg, i.p.). Treatment of animals with cisplatin resulted into the significant body weight changes, oxidative stress, elevated levels of serum biomarkers and histological alterations in the kidney architecture. The BREAF administration reduced relative body weight and organ weight changes in cisplatin-treated rats. The BREAF exhibited nephroprotective effect through the significant reduction of cisplatin-induced rise in the serum creatinine, and blood urea nitrogen levels as well as renal levels of malondialdehyde (MDA) the makers of lipid peroxidation. Additionally, the treatment with BREAF resulted into the increased renal levels of reduced glutathione (GSH), superoxide dismutase (SOD) and catalase activity. Histopathological examination established the nephroprotective effect of BREAF. In conclusion, the anti-oxidant, and anti-inflammatory effects of BREAF has important role underlying its nephroprotective effect.